KARAKTERISTIK I-V ELEKTRODA SUPERKAPASITOR BERBASIS KARBON AKTIF KULIT KACANG BATIK KAWANGKOAN - Tamara, Gersom Jeremia; Polii, Jefferson; Tumimomor, Farly R.; Rampengan, Alfrie M; Mongan, Satyano W. (LPPM Politeknik Saint Paul Sorong, 2024)
The energy crisis is one of the major problems facing the world today, especially electrical energy. Supercapacitors are an alternative solution as an electrical energy storage divais. In this study, batik kawangkoan peanut shell samples have been successfully modified into activated carbon as a supercapacitor electrode. The carbonization process is given a carbonization temperature treatment of 350oC, 400oC, 450oC, 500oC, 550oC which is activated using a 7 M KOH solution by heating in a furnace at 750oC to produce a voltage of 0.966 V, 1.273 V, respectively, 1.295 V, 1.325 V, 1.654 V and currents of 18.56 mA, 23.43 mA, 26.47 mA, 30.53 mA, 48.24 mA which shows that there is a change in the value of current and voltage in supercapacitors, and the best sample is in the sample with 550oC carbonization temperature treatment. Thus, it can be concluded that carbonization temperature has an influence on the current and voltage characteristics of supercapacitor electrodes.